Risk of malignancy index in ovarian tumour for predicting ovarian malignancy by using Jacob’s score - P. S., Rao; Reenu, Bala; Prajwal, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian malignancy is the most common gynecological malignancy after the cancer of the cervix. A woman's risk at birth of ovarian cancer at some time in her life is 1 % to 1.5% and that of dying from cancer is almost 0.5 %. The most commonly occurring ovarian tumors are of epithelial in origin. It has the highest case-fatality ratio of all gynecological malignancies. Hence the early diagnosis is the most important factor for better prognosis. A clinical evaluation of the patient, followed by ultrasonography and CA-125 is helpful. This study aims to determine the role of Risk of Malignancy Index (Jacob’s RMI) in ovarian tumors for prediction of ovarian malignancy. Methods: This is a prospective cohort study. The present study was carried out at department of OBG, in collaboration with the Departments of Radio diagnosis and Pathology, AHRR, New Delhi. 100 patients meeting the inclusion and exclusion criteria were considered. Detailed clinical history, examination and ultrasonography (Abdomen and pelvis) were done. Estimation of CA125 was done thereafter. Calculated JACOBS RMI score was compared with operative surgical staging and histopathological-cytological examination of the specimen. Data obtained thereafter was analysed using appropriate and relevant statistical software. Results: In present study sensitivity of RMI Score in the pre-menopausal women was 66.7% and in post-menopausal women was 83.3%. Specificity of RMI Score in the pre-menopausal women was 96.3% and in post-menopausal women was 81.8%. The positive predictive value in the pre-menopausal women was 40% and in post-menopausal women was 71.4%. The negative predictive value in the pre-menopausal women was 98.7% and in post-menopausal women was 90%. Diagnostic accuracy in a case of premenopausal women was is 95.2% and 82.4% for postmenopausal women. Conclusions: The present study shows that RMI Score helps in identifying effectively those patients who require Staging Laparotomy and hence referral to Gynecologist Oncologist. Patients with ovarian masses with low risk of malignancy index can be treated by minimal access procedures.